Training On Making Website-Based Learning Media And Developing Students' Integrated Skills In Learning English At The Excelsis Deo Community Learning Center (PKBM) Manado - Ali, Muhammad Ilham; Purba, Pebisitona Mesajaya; Kolinug, Ferly Christian (Universitas Malahayati Lampung, 2024)
ABSTRACT This activity explores the implementation of integrated skills in English language learning and the incorporation of website-based learning media at the Excelsis Deo Manado Community Learning Activity Center (PKBM). The research addresses challenges in English education, including low student motivation, conventional teaching methods, and limited use of learning media. An integrated skills approach using children's literature is proposed to enhance language proficiency and cultural awareness. To support this method and overcome media limitations, the study introduces training on creating website-based learning media for teachers. This training covers web design, content management systems, and interactive element creation, aiming to produce engaging online learning environments. The combination of integrated skills teaching and modern, website-based learning media is expected to significantly improve students' English language skills and overall learning experience. This approach not only addresses current educational challenges but also bridges the gap between traditional pedagogy and contemporary learner needs, while providing older teachers with opportunities to adapt to new educational technologies. Keywords: Integrated skills, Website-based learning media, Students and Teacher Training, Children's literature.